2017
DOI: 10.1080/09513590.2017.1332586
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of transdermal testosterone gel 1% (androgel) for poor responders undergoing in vitro fertilization

Abstract: The study was conducted on 110 poor responders undergoing in vitro fertilization (IVF) from October 2015 to July 2016 at the IVF Center of Millitary Medical University, Vietnam. Its aim is to investigate the effectiveness of transdermal androgel before using controlled ovarian stimulation on patients undergoing IVF. A prospective, descriptive study was conducted to compare between the group of patients who used testosterone gel and the group of those who did not in terms of the following indicators: the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Reports have also assessed the efficacy of administering the bioactive androgen, testosterone, in POR patients to improve ovarian response and IVF outcomes (Table 3). Although four RCTs (two with placebo controls) assessing the impact of transdermal testosterone administration for 5-20 days in POR patients showed no significant effect of testosterone pre-treatment (Massin et al 2006, Fabregues et al 2009, Sipe et al 2010, Bosdou et al 2016, since then numerous studies, including a placebo-controlled RCT, have reported on a range of beneficial effects of pre-IVF testosterone pre-treatment (Balasch et al 2006, Kim et al 2011, Mitri et al 2016, Doan et al 2017, Saharkhiz et al 2018. These beneficial effects include improved antral follicle numbers, oocyte retrieval numbers, fertilization rates, embryo implantation rates, embryo quality, clinical pregnancy rates and live birth rates in some women (observations from studies summarized in Table 3).…”
Section: Testosteronementioning
confidence: 99%
“…Reports have also assessed the efficacy of administering the bioactive androgen, testosterone, in POR patients to improve ovarian response and IVF outcomes (Table 3). Although four RCTs (two with placebo controls) assessing the impact of transdermal testosterone administration for 5-20 days in POR patients showed no significant effect of testosterone pre-treatment (Massin et al 2006, Fabregues et al 2009, Sipe et al 2010, Bosdou et al 2016, since then numerous studies, including a placebo-controlled RCT, have reported on a range of beneficial effects of pre-IVF testosterone pre-treatment (Balasch et al 2006, Kim et al 2011, Mitri et al 2016, Doan et al 2017, Saharkhiz et al 2018. These beneficial effects include improved antral follicle numbers, oocyte retrieval numbers, fertilization rates, embryo implantation rates, embryo quality, clinical pregnancy rates and live birth rates in some women (observations from studies summarized in Table 3).…”
Section: Testosteronementioning
confidence: 99%
“…Of these, 936 records were excluded after title/ abstract screening (not relevant to the review). We examined the full text of 18 remaining manuscripts, and, of these, we excluded 10 papers-one paper due to the lack of data concerning CPR and/or LBR [27], one trial reported data not analyzable [28], three papers because the design was observational [29][30][31], and six papers because they were review/metaanalysis [11-13, 21, 32, 33]. Finally, 7 manuscripts were included in the meta-analysis [10,[22][23][24][34][35][36].…”
Section: Study Selectionmentioning
confidence: 99%
“…Recent studies have also been focusing on the pretreatment effect of androgens for POR patients before receiving IVF. However, contradictory results were reported that some studies con rmed the e cacy of androgens in enhancing live birth rate [19][20][21], and some negated the conclusion [19,22]. This could be partly accounted for by the differences in study populations and timing and duration of androgens pre-treatment.…”
Section: Discussionmentioning
confidence: 99%